Fulani Oral Literature and (Un)translatability: The Case of Northern Cameroon Mbooku Poems - Mal Mazou, Oumarou (TTR, 2015)
This paper sets out to examine the translatability of Fulani oral poetry from Northern Cameroon, especially the mbooku genre, in a literary perspective. The corpus is gathered from selected oral poems that were transcribed and translated into German, English and French by different translators. The study reveals that it is possible to translate Fulani poems into European languages so that the target texts perform the same literary functions as the source texts, in spite of linguistic and cultural difficulties that occur during the transfer process. Thus, the author proposes a retranslation in which the content meets the form, taking into account some patterns of European modern poetry. He therefore advocates for retranslations of these poems from a purely literary perspective and would like to see translation studies focus more on the primary source of African orality.